化简:[(x2+4/x)-4]÷(x2-4/x2+2x)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 09:42:58
化简:[(x2+4/x)-4]÷(x2-4/x2+2x)化简:[(x2+4/x)-4]÷(x2-4/x2+2x)化简:[(x2+4/x)-4]÷(x2-4/x2+2x)=[(x²-4x+4)
化简:[(x2+4/x)-4]÷(x2-4/x2+2x)
化简:[(x2+4/x)-4]÷(x2-4/x2+2x)
化简:[(x2+4/x)-4]÷(x2-4/x2+2x)
=[(x²-4x+4)/x]÷[(x+2)(x-2)/x(x+2)]
=[(x-2)²/x]÷[(x-2)/x]
=[(x-2)²/x]×[x/(x-2)]
=x-2
化简:[(x2+4/x)-4]÷(x2-4/x2+2x)
(x2-x)(x2-x-4)+4因式分解
化简x3-x2/x2-x+x2-4x+4/x-2
化简2x2-3/4(4x-6x2)+(x-3x2)求过程!
化简2x2-3/4(4x-6x2)+(x-3x2)求过程!
不等式(x2-4x-5)(x2-8)
约分 1-x2/x2-3x-4
(1-x2)(x2-4x+5)
不等式(x2-4x-5)(x2+1)
化简(x2+2)2-2×(x+2)×(x-2)(x2+4)+(x2-2)2
x2-4x+4
x2-x+4 因式分解
x2+4x+8
5x2—[x2+(4x—x2)—2(x2—3x)]
分式计算:2x/x2-x-2÷(1-x/x+1)-x2+2x/x2-4
分式计算:2x/x2-x-2÷(1-x/x+1)-x2+2x/x2-4
已知x2-4x+1=0,求x2/(x2)2-3x2+1
x2/x2+x+1=1/4,求x2/x4+x2+1的值如题